Preoperative fecal elastase-1 is a useful prognostic marker following curative resection of pancreatic cancer. Issue 5 (May 2017) - Lim, Jin Hong; Park, Joon Seong; Yoon, Dong Sup
Abstract: Background: The clinical relevance of fibrosis with regard to tumor progression is supported by the correlation between fibrosis and poor outcomes. Fecal elastase-1 (FE-1) level has been used to assess exocrine dysfunction of the pancreas and to predict pancreas fibrosis. The aim of this study was to assess the impact of FE-1 on the survival of pancreatic cancer patients. Methods: Between January 2006 and December 2014, 136 patients with pancreatic adenocarcinoma underwent R0 resection at Gangnam Severance Hospital, Korea. Preoperative FE-1 levels were available in 94 patients who were enrolled in the study. Patients were classified into two groups according to preoperative FE-1: "normal" (≥200 μg/g) or "reduced" (<200 μg/g). Results: Median preoperative FE-1 level was 130.1 μg/g (IQR 32.0; 238.3). 62 patients (66.0%) had reduced pancreatic function and 32 patients (34.0%) had normal pancreatic function. The two groups had significantly different disease-free survival (P < 0.001). On multivariate analysis, normal FE-1, no lymph node metastasis and completion of adjuvant chemotherapy were found to be independent prognostic factors for better DFS (P = 0.001, P = 0.017, P = 0.038, respectively). Conclusion: FE-1 is a simple and non-invasive predictive clinical marker for prognosis of pancreatic cancer after attempted curative resection.